Un modelo de gestión de la transformación digital para la innovación - Medellín Cabrera, Enrique Alberto (2024)
Digital transformation is driven by new digital technologies, which are strongly impacting value chains, forms of organization and production, distribution channels, business models and the way in which innovation is carried out in companies and their allies. For this reason, it is important to understand the phenomenon, size it and develop organizational design proposals that facilitate managing it appropriately. Considering the above, this article aims to identify the relationship between digital transformation and innovation in companies, to determine how capabilities can be developed that allow reinforcing innovation processes. To this end, a model is proposed that correlates the management of digital technology and innovation with digital transformation, in such a way that there is a reference framework, guidelines and tools for its organizational deployment.